Pengembangan LKPD Berbasis STEM melalui Kegiatan Pembuatan Paving Block Berbahan Sampah Plastik untuk Meningkatkan Literasi Sains Siswa : Penelitian - Suriyah Satar; Cartika Candra Ledoh; Nurbaya; Hanida Listiani; Amanda Kasanofa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to develop a STEM-based Student Worksheet (LKPD) through a project of producing paving blocks from plastic waste to enhance the science literacy of junior high school students. The study employed a Research and Development (R&D) design using the 4D model, consisting of the define, design, develop, and disseminate stages. Expert validation results indicated that the LKPD achieved a very valid category with an average score of 90%, covering content feasibility, STEM integration, and clarity of procedural steps. The practicality trial involving teachers and students obtained a score of 88.5%, demonstrating that the LKPD is easy to understand and feasible for use in science learning. Its effectiveness was shown through improvements in students’ science literacy, with an N-gain score of 0.65 categorized as medium–high. The project-based learning activity, particularly the creation of plastic-waste paving blocks, successfully fostered active student engagement, strengthened conceptual understanding, and enhanced scientific reasoning in a contextual manner. Therefore, the developed STEM-based LKPD is considered highly potential for implementation in junior high school science learning to cultivate science literacy and environmental awareness among students.